The limits of U.S. military capability lessons from Vietnam and Iraq - Lebovic, James H. (Johns Hopkins University Press, 2010)
In [this book], Lebovic shows how political and psychological factors trumped U.S. military superiority in Vietnam and Iraq, where inappropriate strategies, low stakes, and unrealistic goals mired the United States military in protracted, no-win conflicts.